Pesticide Abuses in India: Challenges and Strategies - Asritha, Chava; Ramesha, N. M.; Satwika, Maharaj (Chronicle of Bioresource Management, 2025)
Pesticides are essential in modern agriculture for protecting crops from pests and diseases, ultimately boosting food production. However, their misuse has serious repercussions for human health and the environment. Improper handling, excessive application, and inadequate protective gear during spraying expose farm workers to harmful chemicals. Chronic exposure has been linked to respiratory issues, neurological disorders, reproductive complications, and increased cancer risks. Additionally, pesticide residues can contaminate soil and water, threatening ecosystems and biodiversity. The overuse of pesticides disrupts ecological balance, leading to declines in beneficial insects, such as bees and other pollinators. This not only affects crop yields but also contributes to the emergence of pesticide-resistant pest strains. To ensure a sustainable agricultural future, it is vital to address these issues through better practices and integrated pest management strategies that minimize reliance on chemical pesticides.